The African Charter on Human and Peoples' Rights the system in practice, 1986-2006 - Evans, Malcolm D. 1959-; Murray, Rachel 1971- (Cambridge University Press, 2008)
The African Charter of Human and Peoples' Rights came into force in 1986, and is unique in that it lacks a precedent. However, little scholarship exists analysing it as an operational system in practice. The success of the first edition of this book led to this updated second edition. Contributors include experts who have been actively involved in the implementation of the Charter - commissioners, NGOs and academics. Offering a detailed evaluation of the Charter as a mechanism for the promotion and protection of human rights in Africa, the contributions cover the Charter's reporting system, the interpretation of different rights by the Commission, the prospects for the African Court on Human and Peoples' Rights and the role of NGOs. This authoritative and comprehensive volume will interest lawyers acting for government and non-governmental organisations, as well as academics and postgraduates